Desenvolvimento de Plataforma Web para Gerenciamento de Dados do Pátio de Estocagem de uma Usina Termelétrica à Carvão - Sousa, Nadson Renan Tomé de (2020)
This work presents a web application developed as a data management platform for the coal yard and laser scanning system. Additionaly, the MACE is proposed to make possible Continuous Review of book inventory balance of coal. Inventory control is one of the most important processes in coal logistics, and continuous inventory control is a major challenge for the mining sector. The magnitude of the problem is due to the fact that the commonly used instruments produce cumulative errors in the estimation of ore mass. Furthermore, the continuous feeding of data in heavy spreadsheets, which are accessible only on computers, make it difficult for managers to access information for decision making. In this way, a data management system for the coal yard was developed, which is associated with a scanning equipment with LiDAR instrumentation for volumetry of the coal piles from stockyard. The yard management system is described from the scanning equipment to ISAA integrated with MACE. About the web platform, the reasons for choosing the language, the software architecture adopted and the result of the screens built in the software are reported. After, MACE is detailed presenting how continuous review of coal stockyard is possible using both mass information not only from volumetry related to densimetry colected in field surveys but also from dynamic weighing systems. In order to go deeper into the MACE methodology, a 9-day simulation was conducted to demonstrate the program’s behavior, which enabled the discussion of the results obtained during this simulation. This work has received funding from Energia Pecém / ANEEL under the grant number PD-07267-0016/2018.